1997
DOI: 10.1073/pnas.94.5.1931
|View full text |Cite
|
Sign up to set email alerts
|

Functional CD40 ligand is expressed on human vascular endothelial cells, smooth muscle cells, and macrophages: Implications for CD40–CD40 ligand signaling in atherosclerosis

Abstract: Increasing evidence supports involvement of inflammation and immunity in atherogenesis. We report here that CD40 ligand (CD40L), an immunoregulatory signaling molecule heretofore considered largely restricted to recently activated CD4 ؉ T lymphocytes, is expressed by human vascular endothelial cells (EC), smooth muscle cells (SMC), and human macrophages in vitro, and is coexpressed with its receptor CD40 on all three cells types in human atherosclerotic lesions in situ. Cultured human vascular EC, SMC, and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
509
9
16

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 684 publications
(544 citation statements)
references
References 36 publications
(36 reference statements)
10
509
9
16
Order By: Relevance
“…Activation of CD40 by binding to CD40 ligand amplifies the production of proinflammatory cytokines by macrophages (24), while ICAM is an adhesion molecule that facilitates recruitment of neutrophils and macrophages to inflammation foci. Thus, induction of these molecules by TREM-1 may lead to initiation of the inflammatory response in acute gout (25).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of CD40 by binding to CD40 ligand amplifies the production of proinflammatory cytokines by macrophages (24), while ICAM is an adhesion molecule that facilitates recruitment of neutrophils and macrophages to inflammation foci. Thus, induction of these molecules by TREM-1 may lead to initiation of the inflammatory response in acute gout (25).…”
Section: Discussionmentioning
confidence: 99%
“…The primary action of CD40-mediated pathway was thought to be restricted to thymus-dependent humoral responses (1). However, a variety of nonlymphocytic cell types have also been shown to express CD40, including monocytes, basophils, dendritic cells, fibroblasts, smooth muscle cells, endothelial cells, and epithelial cells (2)(3)(4)(5). Studies from many groups indicate that CD40 probably plays a more general role in immune regulation (6).…”
mentioning
confidence: 99%
“…Such surface molecules include the contact-dependant CD40-CD154 costimulatory pathways. Endothelial expression of CD154 has previously been described in human cardiac allografts during episodes of ACR (8), and in renal allografts during ACR and CR (6,10,25,26). Although all these studies have demonstrated an increased expression of CD154 during allograft rejection, there have not been, to our knowledge, any experimental studies identifying the specific role of CD40-mediated signalling on endothelium.…”
Section: Discussionmentioning
confidence: 97%